(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The black saxaul (lat. Halóxylon ammodéndron), a vital xerophytic shrub, plays a crucial role in the stabilization and sustainability of desert ecosystems. This study examines the bioecological characteristics of black saxaul in the middle desert region of the Jondor district. Through comprehensive field observations and laboratory analyses, we assessed the plant’s growth patterns, adaptive mechanisms, and ecological contributions. Our findings reveal that black saxaul exhibits remarkable drought resistance, efficient water utilization, and soil stabilization properties, making it an essential species for combating desertification. Understanding the ecological role and adaptive strategies of black saxaul in this arid environment provides valuable insights for desert land management and conservation efforts.